2002
DOI: 10.1080/09537100220122448
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-platelet and platelet-leukocyte interactions induced by outer membrane vesicles from N. meningitidis

Abstract: Meningococcal-derived OMVs as well as purified meningococcal LPS, contribute to increased platelet-platelet and platelet-leukocyte aggregation and may thus be of great importance in the development of microthrombosis and organ dysfunction related to fulminant meningococcal septicemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Nevertheless, other laboratories have observed increased platelet aggregation but not P-selectin expression in response to LPS, whereas fragments of Gram-negative bacteria induced both. 16 Although P-selectin is often considered a good marker of platelet activation, clearly our study and others have observed platelet adhesion independent of P-selectin in response to LPS. Our own results support the lack of P-selectin expression in response to LPS, but our results also suggest that LPS can activate the platelet sufficiently to adhere to fibrinogen in vitro.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, other laboratories have observed increased platelet aggregation but not P-selectin expression in response to LPS, whereas fragments of Gram-negative bacteria induced both. 16 Although P-selectin is often considered a good marker of platelet activation, clearly our study and others have observed platelet adhesion independent of P-selectin in response to LPS. Our own results support the lack of P-selectin expression in response to LPS, but our results also suggest that LPS can activate the platelet sufficiently to adhere to fibrinogen in vitro.…”
Section: Discussionsupporting
confidence: 52%
“…15 A number of other studies, however, have reported some subtle responses of platelets to certain types of LPS and more avid responses to fragments of Gram-negative bacteria. 16 Clearly, a reassessment of the mechanism of platelet activation in endotoxemia is warranted in light of recent reports that platelets are potentially important in different inflammatory scenarios, including sepsis. 13,17,18 19,20 The beneficial effects of GPIIb/IIIa inhibition could be related to reduced recruitment of activated platelets into lungs and liver, where they could cause tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, platelets were shown to be directly activated by Haemophilus somnus and its lipo-oligosaccharide (30). Similarly, platelet activation by outer vesicles from Neisseria meningitidis was shown to play an important role in microthrombosis and organ dysfunction observed in patients with meningococcal septicemia (31). The report by different groups that Toll-like receptor 4, a major receptor for bacterial LPS, is expressed in platelets (32,33) further suggests that these cells can detect and respond to infectious agents.…”
Section: Discussionmentioning
confidence: 98%
“…Platelets can engulf viruses and bacteria (Youssefian et al 2002) and also aggregate in response to whole bacteria (Boukour and Cramer 2005;Byrne et al 2003;Kalvegren et al 2003;Mirlashari et al 2002). Platelets express TLR2, 4, and 9 (Aslam et al 2006;Clark et al 2007).…”
Section: Platelet−derived Products and Function In Host Defensementioning
confidence: 99%